Development of finger type tactile sensor with surface roughness analysis - Shafiyah Abd Rashid (2018)
This research is focused on the development of finger type tactile sensor with surface roughness analysis. Among various human sensations like hearing, sight, taste and smell, touch is a critical co-existing sensation required to interact with surrounding environment. Therefore, it is believed that a good understanding between the touch and surface roughness have potential benefits to the performance of the finger type tactile sensor robot. Even though there is a lot of tactile sensor’s type used in robotic application but there is much less on work has been done on load cell. As far as it is concerned, tactile sensor, vison and audio system is very expensive. Therefore, something cheaper which is load cell is used as a replace for other expensive tactile sensor, in order to modelling and develop a finger type tactile sensor. So, a knowledge study regarding on tactile sensor, touch and grasping are investigated in order to proceed the research. Next, the finger type tactile sensor is designed and developed in SolidWorks software for visual- aided all the view of prototype. To achieve the sensory performance and function of the human fingertips, the design of the fingertips sensor mimics the human fingertips in many aspects, including its size and shape. As objects slide across the structure of surface roughness of the finger type tactile sensor, it generates force that measure in ADC (Volt) that are detected by a loadcells inside the holder. By using Graphical User Interface (GUI), data logging for every extracted graph of each experiment is performed. The developed finger type tactile sensor needs to be tested in order to identify the performance capability of the sensor according to the designed function. A set of 3D printed objects with different values of roughness has been prepared as the sample for this test. Then, for performance validation, Experiment 1: Calibration (Mitutoyo Precision Reference Specimen) has been conducted between using manual robot (Z-arm) and auto robot (Comau Robot). Comau Robot has been chosen as the most suitable robot for the rest of the experiments, then the work is extended to Experiment 2 (Test using Needle File) and Experiment 3 (Test using Tile). The experiment results show that the functionality of the finger type tactile sensor has been successfully validated and proven acceptable for all set of experiment.